Time to Consider Moving Beyond Exclusive Breastfeeding in Southern Africa - Janet M. Wojcicki (MDPI AG, 2017)
While there have been considerable advances in the reduction of mother to child transmission of HIV (MTCT) in sub-Saharan Africa with the advance of anti-retroviral therapies (ART), there remain challenges in the late postpartum period.  Structural issues including food insecurity and stigma make better maternal ART adherence and exclusive breastfeeding unreachable for some women. There are no other scientifically researched feeding options as there have been few studies on different types of mixed feeding practices and risk of HIV infection. Additional studies are warranted to assess detailed feeding practices in HIV exposed infants in relation to clinical outcomes.